Behavior of n-3 polyunsaturated fatty acid ethyl esters in INFOGEST simulated digestion model - Valta, Iida (My University, 2024)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs), such as marine-derived docosahexaenoic acid and plant-derived α-linolenic acid (ALA) are crucial for human health. In dietary lipids, n-3 PUFAs are mainly in triacylglycerol (TAG) form, but their content is often enriched in supplements which requires their transesterification to ethyl esters (EE). Short-term clinical trials have suggested reduced bioavailability of EEs compared to TAGs, possibly resulting from slower hydrolysis of EEs than TAGs by pancreatic lipase. Previous research has indicated that the ingestion of n-3 PUFA EEs with fatty meal improves their bioavailability, possibly because 2-monoacylglycerols (2-MAG) are provided for resynthesis of TAGs in intestinal enterocytes. This study investigated the influence of dietary fat, e.g. TAG and 2-MAG of oleic acid, on the digestion of ALA-EE with the INFOGEST simulated digestion model. In addition, the influence of microencapsulation on digestibility of linseed oil EEs was studied. Encapsulation protects n-3 PUFAs from oxidation, but the effect of polysaccharide-type coating materials on bioavailability is not well understood. Hydrolysis and re-esterification of ALA-EE to glycerol backbone of triolein/2-monoolein were evaluated in the digesta with proton nuclear magnetic resonance spectroscopy. Lipid classes of digestates were identified with liquid chromatography combined with mass spectrometry. Hydrolysis of ALA-EE increased when triolein or 2-monoolein were incubated with excess of ALA-EE (10:1 or 20:1 ALA-EE to triolein/2-monoolein w/w ratio) in comparison to ALA-EE incubated alone in simulated digestion. Prolonging intestinal phase from 2 to 4 hours resulted in statistically significant (p < 0.05) increase in ALA-EE hydrolysis with 2-monoolein at 10:1 ratio. Enhanced hydrolysis in the presence of 2-monoolein occurred likely because 2-monoolein was already in absorbable form, whereas triolein required lipase hydrolysis, thus limiting further hydrolysis of EEs. 2-monoolein could also assist the formation of mixed micelles. ALA was esterified to glycerol backbones of triolein and 2-monoolein in simulated digestion. Approximately half of the 2-monoolein was esterified with ALA after 4-hour intestinal phase at 10:1 ratio. On the other hand, only minor amounts of transesterification product were observed in digestates containing triolein, suggesting that transesterification in intestinal lumen does not explain higher absorption of n-3 PUFA-EEs in the presence of dietary fats. Release of linseed oil EEs from microcapsules in simulated gastrointestinal tract was not restricted by starches that were used as wall materials. Microencapsulation increased the linseed oil EE hydrolysis in comparison to neat linseed oil EEs. Emulsified form of EEs in microcapsules possibly facilitated the action of pancreatic lipase. In addition, results of this thesis revealed the need for optimization of INFOGEST protocol to be more predictive of in vivo n-3 PUFA bioavailability.
Keywords: n-3 polyunsaturated fatty acids, α-linolenic acid, ethyl ester, in vitro digestion, INFOGEST, microencapsulation, bioavailability